Three new species of the genus Rachicerus Walker (Diptera, Xylophagidae) from Brazil - Pujol-Luz, José Roberto; Godoi, Fabio Siqueira Pitaluga De (Zootaxa, 2025)
Xylophagidae is a small group of lower brachyceran flies, comprised by nine extant genera and 135 species. The family occur in all biogeographical regions, except the Afrotropics. The genus Rachicerus is the most speciose containing 70 valid species, which accounts for just over half of the known species of Xylophagidae. Species of Rachicerus are considered rare, both in the wild and in scientific collections, which makes it difficult to investigate individual variations, sexual dimorphism, and other aspects of the morphology of the species in the genus. Only six species of the genus are recorded in Brazil: Rachicerus carrerai Pujol-Luz, 2019; R. lanei Carrera, 1940, R. lopesi Carrera, 1940, R. marcusi Carrera, 1940, R. oliverioi Carrera, 1940 and R. shannoni Carrera, 1945. Here we describe three new species based on four specimens from the Brazilian states: R. isabelae Pujol-Luz sp. nov. (Santa Catarina, 1 female), R. rafaeli Pujol-Luz & Godoi sp. nov. (Amazonas, 1 male and Maranhão, 1 male) and R. victori Pujol-Luz sp. nov. (São Paulo, 1 male). The new species are distinguished from the known species by the number of antennal flagellomeres and abdomen color pattern. A key to identify the Brazilian species of the genus and a distribution map is presented.